Who Gains the Benefits of On-Task Versus Off-Task Self-Assessment? Higher or Lower Proficiency? - Herlinawati, Herlinawati; Abbas, M. Fadhly Farhy (Lectura : Jurnal Pendidikan, 2017)
This study was attempted to investigate the effects of two different types of selfassessment: on-task versus off-task on EFL Indonesian students’ writing performance across different proficiency level. The on-task self-assessment asked the students to self-evaluate their performance immediately after they completed their English writing tasks. The off-task self-assessment asked the students to evaluate their overall performance in a general and somewhat in de-contextualized way. The total number of forty-eight (48) students participated in this study and randomly assigned into two experimental groups. The data was gained from the post-test (essay writing test). The results indicated that the low proficiency students in on-task self-assessment group posed a significant effect and they could self-assess their writing performance more accurately than they had in an off-task format. In conclusion, on-task self-assessment is suggested to be implemented for lower achievers to consolidate their writing performance. However, further research is suggested to conduct to know the students’ experiences in applying on-task and off-task self-assessment as an effective writing strategy.